2006
DOI: 10.1364/oe.14.003631
|View full text |Cite
|
Sign up to set email alerts
|

One-laser interferometric broadband coherent anti-Stokes Raman scattering

Abstract: Abstract:We introduce an interferometric technique for eliminating the non-resonant background of broadband coherent anti-Stokes Raman scattering (CARS) microscopy. CARS microscopy has been used for imaging a number of biological samples and processes, but the studies are mostly limited to detecting lipids in biological systems by probing the C-H stretch. Non-resonant background and incoherent noise sources can easily overwhelm less intense signals from other molecular vibrations. In this study, we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Broadband CARS schemes address this issue by recording a much wider segment of the Raman spectrum. In the broadband approach, the desired spectral information is attained by either resolving the broadband anti-Stokes signal on a CCD-based spectrometer [12][13][14][15] or by Fourier transforming the time-resolved anti-Stokes response. 16,17 The CARS signal yield is typically high enough to record CARS spectra over several hundreds of wave numbers with acquisition times that can be two orders of magnitude faster than what can be achieved with a spontaneous Raman microspectrometer.…”
Section: Introductionmentioning
confidence: 99%
“…Broadband CARS schemes address this issue by recording a much wider segment of the Raman spectrum. In the broadband approach, the desired spectral information is attained by either resolving the broadband anti-Stokes signal on a CCD-based spectrometer [12][13][14][15] or by Fourier transforming the time-resolved anti-Stokes response. 16,17 The CARS signal yield is typically high enough to record CARS spectra over several hundreds of wave numbers with acquisition times that can be two orders of magnitude faster than what can be achieved with a spontaneous Raman microspectrometer.…”
Section: Introductionmentioning
confidence: 99%
“…CARS spectroscopy has provided a useful spectroscopic technique for the past 40 years, despite inherent difficulties as discussed below. However, recent years have witnessed renaissance of interest in CARS spectroscopy (5)(6)(7)(8)(9)(10)(11)(12)(13). This recent progress is driven mostly by technical developments in lasers, optics, electronics and computers, which facilitate the widespread use of this promising spectroscopic tool.…”
mentioning
confidence: 99%
“…We have recently developed a simple ''one-laser'' approach to CARS microspectroscopy, which uses a single-picosecond laser oscillator to generate a broadband continuum that is then mixed with the fundamental beam to generate a full CARS spectrum (15). The large number of already existing Ti:sapphire lasers facilitates the widespread implementation of this method (11,12,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This local oscillator field represents a purely nonresonant CARS signal and can be obtained either separately from a nonresonant sample [69] or from the excitation beam itself; [70] it can also be approximated by the response of the sample to broad-bandwidth-excitation pulses. [71] Various approaches have been demonstrated both in the spectral [69,[71][72][73] and temporal [74][75][76] domain. It has been shown that a time-gated interferometric detection of the CARS signal can be used to realize chemical specificity in optical coherence tomography (OCT) measurements.…”
Section: Measurement Of the Complex Cars Signal Fieldmentioning
confidence: 99%